Bona fide dendritic cells are pivotal precursors for osteoclasts. - Puchner, Antonia; Simader, Elisabeth; Saferding, Victoria; Hofmann, Melanie; Kieler, Markus; Brunner, Julia; Pfeifle, René; Niederreiter, Birgit; Krönke, Gerhard; Schabbauer, Gernot; Georgel, Philippe; Diehl, Gretchen; et al. (Annals of the Rheumatic Diseases, 2024)
OBJECTIVES: Osteoclasts (OCs) are myeloid-derived multinucleated cells uniquely able to degrade bone. However, the exact nature of their myeloid precursors is not yet defined. METHODS: CD11c-diphtheria toxin receptor (CD11cDTR) transgenic mice were treated with diphtheria toxin (DT) or phosphate buffered saline (PBS) during serum transfer arthritis (STA) and human tumour necrosis factor transgenic (hTNFtg) arthritis and scored clinically and histologically. We measured cytokines in synovitis by quantitative polymerase chain reaction (qPCR). We performed ovariectomy in CD11cDTR mice treated with PBS or DT. We analysed CD11cDTR, CD11c-Cre/CX3CR1-STOP-DTR and Zbtb46-DTR-treated mice with DT using histomorphometry and OC of CD11c and Zbtb46 fate reporter mice by fluorescent imaging. We sorted murine and human OC precursors and stimulated them with macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-B ligand (RANKL) to generate OCs. RESULTS: Targeting CD11c+ cells in vivo in models of inflammatory arthritis (STA and hTNFtg) ameliorates arthritis by reducing inflammatory bone destruction and OC generation. Targeting CD11c-expressing cells in unchallenged mice removes all OCs in their long bones. OCs do not seem to be derived from CD11c+ cells expressing CX3CR1+, but from Zbtb46+conventional dendritic cells (cDCs) as all OCs in Zbtb46-Tomato fate reporter mice are Tomato+. In line, administration of DT in Zbtb46-DTR mice depletes all OCs in long bones. Finally, human CD1c-expressing cDCs readily differentiated into bone resorbing OCs. CONCLUSION: Taken together, we identify DCs as important OC precursors in bone homeostasis and inflammation, which might open new avenues for therapeutic interventions in OC-mediated diseases.
EVALuna2:553453